Personality characteristics, anxiety sensitivity, anxiety and depression levels of patients with premenstrual dysphoric disorder - Yildiz, Sevler; Kilicaslan, Asli Kazgan; Kurt, Osman; Ugur, Kerim; Atmaca, Murad (Cukurova Univ, Fac Medicine, 2021)
Purpose: The aim of this study was to evaluate the personality traits, anxiety sensitivity, anxiety and depression levels of patients with Premenstrual dysphoric disorder (PMDD). Materials and Methods: Forty PMDD patients with no psychiatric treatment history and 40 healthy women with similar sociodemographic characteristics and no history of systemic or psychiatric disease were included in the study. Anxiety-Sensitivity-Index-3 (ASI-3), Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), and the Eysenck Personality Questionnaire-Revised Abbreviated (EPQR-S) were administered to all participants. Results: The patient group's EPQR-S neuroticism, psychoticism, lying subscales and total scores were significantly higher than the control group's scores. The ASI-3 physical, cognitive, social sub-dimensions and total score of the patient group were found to be significantly higher than the control group's score. The BDI and BAI scale scores of the patient group were found to be significantly higher than the scores of the control group. Conclusion: In women with high anxiety sensitivity, psychotic and neurotic personality traits, this may affect the development of PMDD or the course of the disease.
Keywords: Premenstrual dysphoric disorder; anxiety; depression; anxiety sensitivity; personality traits